2014
DOI: 10.1590/s1516-89132014005000003
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli isolated from Algerian goat's milk as adjunct culture in dairy products

Abstract: In this study, nineteen Lactobacillus isolated from Algerian goat's milk, 13 belonging to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Pailin et al [39] reported similar finding, where all studied LAB isolates demonstrated ability to form clear zone on skim milk. Likewise, majority of the LAB isolated from Algerian goat’s milk [40] and Egyptian Ras cheese [41] have demonstrated the ability to produce clear hydrolysis zone on skim milk agar. This implied that majority of LAB possessed extracellular proteolytic activity.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Pailin et al [39] reported similar finding, where all studied LAB isolates demonstrated ability to form clear zone on skim milk. Likewise, majority of the LAB isolated from Algerian goat’s milk [40] and Egyptian Ras cheese [41] have demonstrated the ability to produce clear hydrolysis zone on skim milk agar. This implied that majority of LAB possessed extracellular proteolytic activity.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…2B, reached a final viable count of more than 10 7 CFU per gram, which can be considered satisfactory for a potential probiotic in cheeses (Karimi, Mortazavian, & Da Cruz, 2011). To the best of the authors' knowledge, although L. plantarum strains have been used successfully as adjunct cultures in other semi-hard and semi-ripened cheeses (Milesi, McSweeney, & Hynes, 2008;Milesi, Vinderola, Sabbag, Meinardi, & Hynes, 2009;Minervini et al, 2012;Ortigosa, Arizcun, Torre, & Izco, 2005;Songisepp et al, 2012), few studies have been carried out concerning the possible use of L. pentosus strains as adjunct cultures in dairy products, especially those isolated from fermented vegetables (Ciocia et al, 2013;Marroki & Bousmaha-Marroki, 2014). Another fundamental feature that a probiotic added to a food matrix has to possess is the capability of overcoming the conditions found in the digestive tract and of reaching the intestine in adequate amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Positive hemolytic activity (ability to breakdown red blood cells) halt the underlying epithelial layer whereas positive gelatinase activity (ability to hydrolyse gelatin) breakdown the protective lining of the GIT. Absence of hemolytic, gelatinase and lipase activity makes a strain non-virulent, indicating its selection for probiotic strain 30 .…”
Section: Safety Assessment Of Selected Isolatesmentioning
confidence: 99%